Crisis Of Moral Education Causes Bullying At Elementary School - Zulvia Misykah; Dewi Sartika Panggabean; Yasuli Bindulem (International Journal of Advanced Research, 2024)
Education is a bridge to educate the nation's generation or children. The world of education has a very important role in the progress of this country. It is through this world of education that the younger generation or children of the nation are able to master knowledge from several domains, namely the cognitive, affective and psychomotor domains which contain moral education. However, the development of moral education for the nation's generation in the current era of globalization is quite apprehensive, such as bullying that often occurs in the world of education. These problems are strong evidence that the world of education in the current era of globalization is experiencing a crisis of moral education. So that a clear emphasis on moral education is needed from the beginning or from an early age carried out by parents as the first school for children and then followed by the role of the teacher as the child's second school in the world of education. The fact that the lack of attention from parents and teachers at school regarding children's moral education will also have a big impact on children's moral. This study uses the literature review method, which is the process by which researchers place, obtain, read, and evaluate research literature related to the issue to be studied.